Mengelola konflik dalam implementasi corporate social responsibility dan dampaknya terhadap lingkungan - Nugroho Hasan (Environment Conflict, 2024)
Background: Law No. 40 of 2007 requires companies to implement CSR, covering social, economic, and environmental responsibilities. Although CSR is often perceived as a burden, its implementation is crucial for business sustainability. This study aims to analyze the development of CSR in Indonesia, its challenges, and solutions. Method: This research analyzes the implementation of CSR in Indonesia, the conflicts between companies and communities, as well as conflict resolution strategies based on democratic principles. Findings: The development of CSR in Indonesia has been driven by regulations such as the Limited Liability Company Law and Government Regulation 47/2012. Conflicts in implementation often arise due to differences in perceptions and stakeholder interests. Conflict management requires transparency, participation, and resolution strategies based on ethical leadership to build trust and enhance the effectiveness of CSR programs. Conclusion: CSR conflict management in Indonesia emphasizes stakeholder engagement, community empowerment, and the principles of transparency, accountability, and social justice to achieve harmony between companies and communities. Novelty/Originality of this article: The novelty of this research lies in its approach to analyzing conflict management in CSR implementation in Indonesia, focusing on conflict resolution strategies based on democratic principles and ethical leadership. This study highlights the importance of transparency, participation, and accountability in fostering harmonious relationships between companies and communities, which has not been widely discussed in the context of Indonesia's CSR regulations. Furthermore, this research offers new solutions by integrating the principles of social justice and community empowerment into CSR strategies, strengthening the role of local stakeholders for program sustainability.